A-Z of Popular Garden Plants - Consultant Editor: Titchmarsh, Alan (London Octopus Books Ltd., 1993)
With over 250,000 different species of flowering plants in the world, choosing the right plant poses a bewildering choice for even the most experienced gardener. This A-Z aims to make the choice easier by providing a guide to proven favourites.
Include Sketches, Color Illustrations and Index.
Keywords: Plants, Ornamental -- Gardening -- Great Britain